2009
DOI: 10.1080/15325020902925506
|View full text |Cite
|
Sign up to set email alerts
|

Late Effects of Trauma: PTSD in Holocaust Survivors

Abstract: Participants in this study were Jewish Holocaust survivors (N ¼ 89) divided into groups depending on the type of trauma they had experienced. As compared to the control group, posttraumatic stress disorder (PTSD) symptoms were clearly more persistent in the trauma group. The most salient PTSD symptoms (primarily avoidance and increased arousal) were noted in those who survived hiding on the ''Aryan side.'' Men were more at risk for reexperiencing trauma than women, who were more prone to avoidance or numbing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
1
5
0
1
Order By: Relevance
“…The fact that hidden Jewish children still report severe posttraumatic symptoms 65 years later is consistent with other studies (Cohen et al, 2003;Lis-Turlejska et al, 2008). Some researchers even found that the severity of PTSD was as high or even higher for hidden children than other types of Holocaust survivors, especially with respect to avoidance and arousal (Yehuda et al, 1997;Prot, 2010). It is possible that the inability to disclose their experiences may partly explain this phenomenon, as disclosure of traumatic experiences is related to better mental and physical health among Holocaust survivors (Finkelstein & Levy, 2006).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The fact that hidden Jewish children still report severe posttraumatic symptoms 65 years later is consistent with other studies (Cohen et al, 2003;Lis-Turlejska et al, 2008). Some researchers even found that the severity of PTSD was as high or even higher for hidden children than other types of Holocaust survivors, especially with respect to avoidance and arousal (Yehuda et al, 1997;Prot, 2010). It is possible that the inability to disclose their experiences may partly explain this phenomenon, as disclosure of traumatic experiences is related to better mental and physical health among Holocaust survivors (Finkelstein & Levy, 2006).…”
Section: Discussionsupporting
confidence: 66%
“…Some studies have found age to be negatively correlated with posttraumatic stress (Prot, 2010), while others have observed a positive correlation (Cohen et al, 2002;Dyregrov, Gjestad, & Raundalen, 2002;Keilson, 1992;Schaal & Elbert, 2006). Three studies, however, failed to find such clear associations (Cohen, Dekel, Solomon, & Lavie, 2003;Lis-Turlejska et al, 2008;Yehuda, Schmeidler, Siever, Binder-Brynes, & Elkin, 1997).…”
Section: Literature Review and Hypothesesmentioning
confidence: 87%
“…CALAS survivors went through the Holocaust as adults (none of them were less than 18 years old in 1945), whereas IMAS survivors were in their late adolescent years or young adulthood during the Holocaust (30.5% were less than 18 years old in 1945). Previous studies demonstrated the divergent effects of the Holocaust among survivors in different age groups during WWII (Lev-Wiesel & Amir, 2003;Prot, 2010). Thus, it is important to note that notwithstanding their age differences during and after WWII, survivors from our two samples were also in different life periods that embody unique developmental processes.…”
Section: Strengths Limitations Caveats and Conclusionmentioning
confidence: 86%
“…This study accounted for the setting in which survivors went through the Holocaust, thus differentiating between concentration camp (CC) survivors and exposed survivors (survivors who were in other settings, such as being (Joffe et al, 2003;Letzter-Pouw & Werner, 2005), similarly (Dekel & Hobfoll, 2007;Yehuda, Schmeidler, Siever, Binder-Brynes, & Elkin, 1997), or even better than other survivors (Lomranz, 2005;Prot, 2010). The present study also compared these groups of Holocaust survivors to European-origin Jews who immigrated either before or after WWII to Israel.…”
Section: Overview Of the Current Study And Hypothesesmentioning
confidence: 93%
See 1 more Smart Citation